PENGARUH ONLINE SHOP TERHADAP MINAT BELI MAHASISWA STAIN PAREPARE - Nasri Hamang; Sulfiana Rahmat; Nurhakki nurhakki (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2016)
This study discusses the frequency of visits of students and influence online shop online shop use the buying interest of students. and to determine the effect of Use Online Shop to purchase interest students STAIN Pare Pare. The theory used in this research is the theory of the satisfaction and usage (uses and graditfications Theory) This study uses a quantitative approach used in collecting data and observations and questionnaires. The population of this research is the students who use online sites STAIN shop located in Pare Pare and the sample is taken every STAIN departments in Pare Pare. The sampling technique used was simple random sampling technique, data analysis technique that is the product moment correlation, mancari correlation between (X) and (Y). Visit online shop Students STAIN Pare Pare is quite attractive for display Online shop itself is so interesting and provide some easiness for its users like the ease of ordering and delivery of goods, as well as with the price of the goods it offers easier compared to the price of the items in stores. Media Blackberry Messenger is the most demanding media students in using the site's online shop because the media has many advantages compared with other media, and most meet the needs of users. This is evidenced by the in-depth data analysis using product moment correlation for correlations between variables x (use online shop) and y variables (the buying interest of students). The result obtained by the value of n or the number of samples investigated, the equal liberty is 57-2 = 55 with a standard error of 5%, the r-table 0,266, This is true provided that if r-count is greater than r-table (r-count> r the table was) then H1 accepted and H0 is rejected. Vice versa if r-count is smaller than r-table (r-count <r-table) then H1 (there is the effect of using onlie shop to purchase interest of students STAIN Pare Pare) is rejected and H0 (there is no influence of use onlie shop on buying interest STAIN students Parepare) is obtained hasilt diterima.Penelitian r-count 0578 where r is calculated in terms of a hypothetical conclusions based on sampled data and r-table 0266 aritnya that r-count> r-table, then H0 rejected H1 accepted and means a significant positive correlation between the variables X and Y. conclusion, it is evident that there is the effect of the use of the online shop to purchase interest students STAIN Pare Pare.